Autologous Minimally Manipulated Homologous Adipose Tissue (AMHAT) for Treatment of Nonhealing Diabetic Foot Ulcers. Issue 10 (28th October 2022) - Armstrong, David G.; Harris, Steven G.; Rasor, Zachary; Zelen, Charles M.; Kim, Jeehee; Swerdlow, Mark; Isaac, Adam L.
Abstract : Background: Diabetic foot complications are increasingly burdensome for patients, clinicians, and society. Development of innovative therapies to support good quality basic care is a priority among those with an interest in this area. One of these involves scanning and printing tissues to match and conform to a defect (so-called 3D printing). Methods: A single-arm pilot study of ten consecutive patients with a history of a chronic diabetic foot ulcer (DFU), treated with autologous minimally manipulated homologous adipose tissue (AMHAT), dispensed by a specialized 3D bioprinter, Dr. INVIVO, was performed. Patients with nonhealing DFUs present for more than 4 weeks and refractory to standard-of-care therapies were included. Wounds were treated with a single application of AMHAT, and then followed up weekly for up to 12 weeks, or until the wounds healed. The primary outcome measure was complete epithelialization of the wound up to 12 weeks after the treatment. Secondary outcome measures included wound size and/or volume reduction, assessment of ulcer grade, and time to closure. Results: Five wounds were healed by 5 weeks and one at 8 weeks. The mean percent area reduction at 12 weeks was 78.3% (SD: 33.23). Complete closure was achieved in 60% of wounds. The mean time to closure in these wounds was 49.1 days (95% CI, 29.9–68.3). No adverse events were reported. Conclusions: Single treatment of bioprinted AMHAT appears to be a safe and potentially effective treatment modality for patients with chronic DFUs. Further studies are warranted to explore the full potential of 3D bioprinting for tissue repair in this high-risk population.